Gaining Insight into the Effect of Organic Interface Layer on Suppressing Ion Migration Induced Interfacial Degradation in Perovskite Solar Cells. (12th July 2020) - Ning, Jiaoyi; Zhu, Yanan; Hu, Zhao; Shi, Yuhao; Ali, Muhammad Umair; He, Junpeng; He, Yaowu; Yan, Feng; Yang, Shihe; Miao, Jingsheng; Meng, Hong
Abstract: Ion migration induced interfacial degradation is a detrimental factor for the stability of perovskite solar cells (PSCs) and hence requires special attention to address this issue for the development of efficient PSCs with improved stability. Here, an "S‐shaped, hook‐like" organic small molecule, naphthalene diimide derivative (NDI‐BN), is employed as a cathode interface layer (CIL) to tailor the [6, 6]‐phenylC61‐butyric acid methylester (PCBM)/Ag interface in inverted PSCs. By realizing enhanced electron extraction capability via the incorporation of NDI‐BN, a peak power conversion efficiency of 21.32% is achieved. Capacitance–voltage measurements and X‐ray photoelectron spectroscopy analysis confirmed an obvious role of this new organic CIL in successfully blocking ionic diffusion pathways toward the Ag cathode, thereby preventing interfacial degradation and improving device stability. The molecular packing motif of NDI‐BN further unveils its densely packed structure with π–π stacking force which has the ability to effectually hinder ion migration. Furthermore, theoretical calculations reveal that intercalation of decomposed perovskite species into the NDI clusters is considerably more difficult compared with the PCBM counterparts. This substantial contrast between NDI‐BN and PCBM molecules in terms of their structures and packing fashion determines the different tendencies of ion migration and unveils the superior potential of NDI‐BN in curtailing interfacial degradation. Abstract : An "S‐shaped, hook‐like" naphthalene diimide derivate, NDI‐BN, is adopted as a cathode interface layer in inverted perovskite solar cells and good power conversion efficiency of 21.32% with enhanced stability is achieved. The relationship between the molecular packing motif of the organic interface layer and the interfacial degradation mechanism is explored.